Under simulated microgravity and gravity, anthocyanin is regulated by DcaWRKY2 in Dendrobium catenatum leaves - Hou, Tianze; Zheng, Baoqiang; Peng, Fucheng; Jiang, Zehui; Zhang, Wenbo; Wang, Yan (Frontiers in Plant Science, 2025)
Long-term space missions will require high-quality plants that are edible, medicinal, and ornamental, to support the physical and mental health of astronauts under altered gravity conditions. Anthocyanins play a key role in enhancing the medicinal and edible value and ornamental properties of plants. However, under simulated microgravity, the transcription control of anthocyanin biosynthesis is not clear. Here, in order to investigate the influences of simulated microgravity on the anthocyanin accumulation further, clones of Dendrobium catenatum were exposed for 20 days to simulated microgravity conditions. The anthocyanin content in Dendrobium catenatum leaves increased in the simulated microgravity conditions compared with that in gravity-treated clones. Furthermore, based on the transcriptome sequencing, differentially expressed genes (DEGs), and weighted gene co-expression network analysis combined with RT-qPCR, we identified one WRKY gene, DcaWRKY2, from a Dendrobium catenatum under simulated microgravity conditions, which indicated that DcaWRKY2 may be involved in anthocyanin biosynthesis under simulated microgravity conditions. A more in-depth analysis evaluating the function of DcaWRKY2, transcription factor gene DcaWRKY2, was silenced by virus-induced gene silencing under gravity conditions, which resulted in the increase of anthocyanin accumulation in leaves, and the expression levels of anthocyanin biosynthesis pathway (ABP) structural genes, including DcaCHS, DcaCHI, DcaF3H, DcaDFR, and DcaANS were increased significantly. This research provides new insights into how altered gravity can affect anthocyanin synthesis in plants and illuminated the regulatory effects of DcaWRKY2 on the leaves’ pigmentation and anthocyanin biosynthesis in Dendrobium catenatum under gravity and simulated microgravity.